2017
DOI: 10.4314/tjpr.v16i8.27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <i>in vitro</i> antiprotozoal activity of some 2- amino-4-phenyloxazole derivatives

Abstract: Purpose: To prepare some 2-amino-4-(p-substituted phenyl)-oxazole derivatives and to evaluate their in vitro antiprotozoal activity against Giardia lamblia and Trichomonas vaginalis. Methods: The 2-amino-4-(p-substituted phenyl)-oxazoles (a-g) were synthesized by microwave (MW) irradiation of mixtures of p-substituted 2-bromoacetophenones and urea in dimethylformamide (DMF). All compounds were identified by 1 H and 13 C nuclear magnetic resonance (NMR) spectroscopy and lowand high-resolution mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Oxazole is the parent compound for a vast class of heterocyclic aromatic organic compounds. These are azoles with an oxygen and a nitrogen separated by one carbon [9]. Oxazoles are aromatic compounds but less so than the thiazoles.…”
Section: Chemistry Of Oxazolementioning
confidence: 99%
“…Oxazole is the parent compound for a vast class of heterocyclic aromatic organic compounds. These are azoles with an oxygen and a nitrogen separated by one carbon [9]. Oxazoles are aromatic compounds but less so than the thiazoles.…”
Section: Chemistry Of Oxazolementioning
confidence: 99%
“…Oxazole and its derivatives are used in treatment of various types of illness [8] . Oxazole shows numerous biological activities such as anti-bacterial [9,10] , antifungal [11,12] , agonist of free fatty acid receptor (GPR40) [13] , highly selective histone deacetylase 6 (HDAC6) [14] , anticancer [15,16] , vegetative growth factor [17] , anti-tubercular, anti-leishmanial [18] , antiprotozoal [19] and anti-inflammatory [20] . Apart from these pharmacological activities, oxazole derivatives can also be used as anti-corrosive agent for stainless steel, dyes [21] , anti-ageing [22] , antioxidant [23] , metabolism enhancing agent [24] , pesticides and herbicides [6] .…”
Section: Pharmacological Activities Of Oxazolementioning
confidence: 99%
“…This gives a very good chance of making 4, 5-disusbtituted oxazolines and 5-substituted oxazoles. Carballo et al [19] synthesised and tested seven derivatives of 2-amino-4-(p-substituted phenyl)oxazole as an antiprotozoal agent in vitro against Giardia lamblia and Trichomonas vaginalis. These oxazole derivatives were synthesized under microwave irradiation of a mixture of p-substituted 2-bromoacetophenone and urea in the presence of DMF.…”
Section: Microwave Assisted Synthesis Of Oxazole Derivativesmentioning
confidence: 99%
“…In this initial phase, α-bromo-4′-methylacetophenone ( 5 ) was used as the starting building block to react with urea ( 6 ) (Table ). This reaction has been reported in six studies, , and the yield for the formation of 7 was reported in only one case (21%) . For the first step, we focused our interest on optimizing parameters such as the solvent and the stoichiometric ratio and determining whether microwave (MW) irradiation is more efficient than conventional heating.…”
mentioning
confidence: 99%
“…This reaction has been reported in six studies, 21,25−29 and the yield for the formation of 7 was reported in only one case (21%). 25 For the first step, we focused our interest on optimizing parameters such as the solvent and the stoichiometric ratio and determining whether microwave (MW) irradiation is more efficient than conventional heating. With regard to the solvent, first attempts were made using acetonitrile, ethanol, dimethoxyethane (DME), and PEG-400, as already reported in the literature for this kind of reaction.…”
mentioning
confidence: 99%